Changes in Sports Participation Trends: A Comparative Theoretical Analysis of the Case of the Municipality of Zaragoza - Celia Marcen; Irela Arbones-Arque; Dominic Malcolm (Social Sciences)
This paper seeks to test the explanatory potential of different sociological perspectives in relation to the development of new sport models that reflect the growth of leisure sport participation in urban outdoor places and the decline in traditional practices in associations and clubs. In this regard, this study employs an analytical framework to examine global trends, with a particular focus on the specific context of the municipality of Zaragoza (Spain). With a multi-method approach, a 10-year-period dataset (2009–2019) incorporating sport participation surveys, observational data, and a focus group study is analysed. Three theories are tested: Maffesoli’s neo-tribes; neo-Bourdieuian ideas about urban subcultures; and Elias’s theory of civilizing processes. The results show a congruence between the three theories regarding identity negotiation, commodification, and community sense. However, disparities were found between the three theories, with one or more of them exhibiting an absence of class consciousness that supports subcultural interpretation and distinct notions of change versus continuity of the analyzed phenomena. This paper concludes that recent sports participation trends are best explained with reference to the quest of excitement and using healthism as a dominant ideology or social imperative.